Utilizing physiologies, transcriptomics, and metabolomics to unravel key genes and metabolites of Salvia miltiorrhiza Bge. seedlings in response to drought stress - Zhang, Yu; Zhang, Hong; Zhang, Yuru; Wang, Di; Meng, Xue; Chen, Juan (Frontiers in Plant Science, 2025)
Drought stress inhibits Salvia miltiorrhiza Bunge (S. miltiorrhiza) seedling growth and yield. Here, we studied the effects of drought stress on the different parts of S. miltiorrhiza seedlings through physiological, transcriptomic, and metabolomics analyses, and identified key genes and metabolites related to drought tolerance. Physiological analysis showed that drought stress increased the accumulation of hydrogen peroxide (H2O2), enhanced the activity of peroxidase (POD), decreased the activity of catalase (CAT) and the contents of chlorophyll b and total chlorophyll, reduced the degree of photosynthesis, enhanced oxidative damage in S. miltiorrhiza seedlings, and inhibited the growth of S. miltiorrhiza plants. Transcriptome analyses revealed 383 genes encoding transcription factors and 80 genes encoding plant hormones as hypothetical regulators of drought resistance in S. miltiorrhiza plants. Moreover, differentially expressed genes (DEGs) and differentially expressed metabolites (DEMs) are involved in a variety of biological processes, such as proline and glycine betaine metabolism, and biosynthesis of tanshinones and phenolic acids. Additionally, it has barely been reported that the AHL gene family may be involved in regulating the neocryptotanshinone biosynthesis. In conclusion, our results suggest that drought stress inhibits S. miltiorrhiza seedling growth by enhancing membrane lipid peroxidation, attenuating the antioxidant system, photosynthesis, and regulating proline and glycine betaine metabolism, transcription factors and plant hormones, and tanshinones and phenolic acid metabolism pathways. This study provides new insights into the complex mechanisms by which S. miltiorrhiza responds to drought stress.